2017
DOI: 10.1093/infdis/jix230
|View full text |Cite
|
Sign up to set email alerts
|

Parasites Causing Cerebral Falciparum Malaria Bind Multiple Endothelial Receptors and Express EPCR and ICAM-1-Binding PfEMP1

Abstract: These results underpin the significance of EPCR binding in pediatric malaria patients that require hospital admission, and support the notion that complementary receptor interactions of EPCR binding PfEMP1with ICAM-1 amplifies development of severe malaria symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 33 publications
0
58
0
Order By: Relevance
“…The CIDR␣1-mediated attachment of infected erythrocytes to EPCR is a potential target for vaccines to prevent severe malaria. Characterization of PfEMP1 expressed in severe malaria indicates that all EPCR-binding CIDR␣1 subtypes can precipitate disease (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Thus, an effective malaria vaccine targeting PfEMP1 probably has to target most, if not all, CIDR␣1 subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CIDR␣1-mediated attachment of infected erythrocytes to EPCR is a potential target for vaccines to prevent severe malaria. Characterization of PfEMP1 expressed in severe malaria indicates that all EPCR-binding CIDR␣1 subtypes can precipitate disease (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Thus, an effective malaria vaccine targeting PfEMP1 probably has to target most, if not all, CIDR␣1 subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of immunoepidemiological evidence (recently reviewed in Bull and Abdi [10]) has converged on a subset of PfEMP1 molecules being the main target of IgG protecting against severe malaria. Recent studies of PfEMP1 gene expression in patients have identified the subset of PfEMP1 molecules associated with development of severe malaria symptoms, including severe anemia and cerebral malaria (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). This subset is defined by carrying a so-called CIDR␣1 domain mediating tethering to endothelial cells through binding to endothelial protein C receptor (EPCR) (22).…”
mentioning
confidence: 99%
“…More recently parasites causing cerebral malaria were shown to express var genes encoding for PfEMP1s that bind EPCR and ICAM‐1 in static binding assays (Tuikue Ndam et al , ). Parasites from children with cerebral or uncomplicated malaria were characterized in their transcribed var gene and the binding properties of iRBC collected on admission.…”
Section: Binding Properties Of Different Plasmodium Falciparum Clinicmentioning
confidence: 99%
“…And, when the binding capacity to CD36, ICAM‐1 or EPCR was investigated, adhesion to EPCR and ICAM‐1 was more common in cerebral malaria‐causing parasites than in uncomplicated malaria‐causing parasites. Furthermore, parasite isolates from cerebral malaria patients more frequently exhibited binding to both ICAM‐1 and EPCR, whereas binding to CD36 was more frequent in uncomplicated malaria than cerebral malaria patients (Tuikue Ndam et al , ).…”
Section: Binding Properties Of Different Plasmodium Falciparum Clinicmentioning
confidence: 99%
“…A particular association with cerebral symptoms was found for parasites expressing PfEMP1s that combine both an EPCR-binding CIDRα1 domain and a DBLβ domain that can bind to ICAM-1, allowing simultaneous binding of infected erythrocytes to both ligands [38,42,43] (Figure 1). (A) The architecture of PfEMP1 ectodomains displayed on the surface of erythrocytes infected with P. falciparum.…”
Section: Do Anti-disease Immunogens Have a Place In Future Malaria Vamentioning
confidence: 99%